QUALITY OF CURED FISH FROM TAMILNADU COAST - JOSEPH, K GEORGE; MURALEEDHARAN, V; KALAIMANI, N; NAIR, T. S UNNIKRISHNAN (Fishery Technology, 2017)
Results of studies of chemical, bacteriological and organoleptic quality of cured fish collected from four major curing centres along the Tamilnadu coast are reported. Only 32.43% of the samples had moisture level below 35%, 0.9% had salt 25% and above. None of the samples showed acid insoluble ash below 1.5% . The main defects were unhygienic processing, inadequate salting, use of poor quality salt and incomplete Â drying. Recommendations for improvement of quality are given.